Ovarian and Oocyte Morphology During the Spring-Summer and Fall-Winter in Queens (Felis catus) Kept in a Tropical Climate - de Camargo, Laiza Sartori [UNESP]; Rizzoto, Guilherme; de Carvalho, Jaqueline Candido [UNESP]; Cardoso, Karym Christine de Freitas; Tavares, Denise Cláudia; Conforti, Valéria Amorim; Honsho, Cristiane dos Santos; de Souza, Fabiana Ferreira [UNESP] (Elsevier, 2021)
The objective of this study was to investigate the effects of seasonality and phase of the estrous cycle on ovarian and oocyte morphology in domestic cats kept in a tropical region. The ovaries from 23 queens were collected after elective ovariohysterectomy at different stages of the estrous cycle and were classified according to the season upon collection (spring/summer vs. fall/winter). Based on the findings, we concluded that queens in tropical regions experience no seasonal influence on oocyte quality, but there is a minimal effect on ovarian morphology, with an increase in ovarian length during proestrus/estrus in the spring/summer period.
Keywords: estrous cycle; feline; seasonality